2020
DOI: 10.1001/jamanetworkopen.2020.12005
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Sensitivity and Specificity of Patient-Collected Lower Nasal Specimens for Severe Acute Respiratory Syndrome Coronavirus 2 Testing

Abstract: Participant 27 was asymptomatic but had been exposed to sudden acute respiratory syndrome coronavirus 2 by close contact 4 days before the study swab was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 1 publication
2
66
0
Order By: Relevance
“…Our data support that self-sampling by OP swab is dependable, and thus provides an alternative method for unsupervised or remotely supervised sample acquisition outside of a healthcare setting. OP and other methods of self-sampling could enable sample processing by mail, which can greatly enhance testing coverage 28,29 . Another advantage of self-collection is that the person can control the swabbing and stop if they experience extreme discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support that self-sampling by OP swab is dependable, and thus provides an alternative method for unsupervised or remotely supervised sample acquisition outside of a healthcare setting. OP and other methods of self-sampling could enable sample processing by mail, which can greatly enhance testing coverage 28,29 . Another advantage of self-collection is that the person can control the swabbing and stop if they experience extreme discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that patient-collected foam nasal swabs were comparable to health care worker-collected NP swabs for collecting SARS-CoV-2 virus, providing a safer and less invasive sampling method [ 5 ]. Similarly, another independent study demonstrated that patient-collected nasal swabs were comparable to health care worker-collected oropharyngeal or nasal swabs [ 6 ]. These results validate findings for influenza testing [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with results in the U.S. population and in MN specifically during the period these samples were collected. The sensitivity of our screening tests might have been low due to the use self-collected NPS, although recent studies report self-collection protocols to have acceptable sensitivity 9,10 . Tests among symptom-free individuals could also have reduced sensitivity, however, prior studies in asymptomatic pregnant women 11,12 and residents of long-term care facilities 13 Our results suggest that while the healthcare worker force is very likely to be at increased relative risk for infection compared to the general population 8 , the point prevalence of SARS-CoV-2 infection was low in symptom-free Minnesota healthcare workers.…”
Section: Discussionmentioning
confidence: 99%